2002
DOI: 10.1136/jmg.39.7.463
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and functional analysis of the von Hippel-Lindau (VHL) tumour suppressor gene promoter

Abstract: The VHL gatekeeper tumour suppressor gene is inactivated in the familial cancer syndrome von HippelLindau disease and in most sporadic clear cell renal cell carcinomas. Recently the VHL gene product has been identified as a specific component of a SCF-like complex, which regulates proteolytic degradation of the hypoxia inducible transcription factors HIF-1 and HIF-2. pVHL is critical for normal development and mRNA expression studies suggest a role in nephrogenesis. Despite the importance of VHL in oncogenesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 49 publications
3
24
0
Order By: Relevance
“…Nevertheless, the 11 bp duplication is located within the promoter region of the VHL gene, in the vicinity of the main transcription initiation site (Kuzmin et al 1995), and within the putative binding site of several transcription factors (Zatyka et al 2002). We therefore investigated the possibility that the variant could alter transcription of the gene from the affected allele.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the 11 bp duplication is located within the promoter region of the VHL gene, in the vicinity of the main transcription initiation site (Kuzmin et al 1995), and within the putative binding site of several transcription factors (Zatyka et al 2002). We therefore investigated the possibility that the variant could alter transcription of the gene from the affected allele.…”
Section: Resultsmentioning
confidence: 99%
“…This genetic insight linked several lines of evidence that indicated that the HIF-a was subjected to PHD-mediated hydroxylation under normoxic conditions, requiring the presence of iron, 2-oxoglutarate, PHDs, and oxygen. Once modified by the-OH group, HIF-a can be captured by pVHL, which then delivers HIF-a to an E3-ubiquitin ligase complex through binding of Elongins B and C, and subsequent proteasomal degradation [Hon et al, 2002;Ivan et al, 2001;Jaakkola et al, 2001;Jiang et al, 2003;Maxwell et al, 1999;Min et al, 2002;Vengellur et al, 2003;Wykoff et al, 2000;Yu et al, 2001;Zatyka et al, 2002;Zhu and Bunn, 2001]. The interplay of these proteins, centered on the presence of an-OH group, results in a direct molecular oxygen sensor.…”
Section: The Vhl Gene and Functionmentioning
confidence: 99%
“…VHL analysis in C. elegans has produced strong evidence that a group of genes is regulated by pVHL in a manner independent of oxygen levels [Bishop et al, 2004]. Furthermore, multiple groups have reported microarray analyses in mammalian cell lines that indicate a role for pVHL independent of its interaction with HIF [Bluyssen et al, 2004;Bommi-Reddy et al, 2008;Jiang et al, 2003;Wykoff 2000Wykoff , 2004Zatyka et al, 2002]. Other roles of pVHL include microtubule stability [Hergovich et al, 2003], microtubule orientation [Schermer et al, 2006], cilia formation [Esteban et al, 2006;Lolkema et al, 2008;Lutz and Burk, 2006;Schermer 2006;Thoma et al, 2007], regulation of senescence [Young et al, 2008], cytokine signalling [Wu et al, 2007], collagen IV regulation [Grosfeld et al, 2007;Kurban et al, 2008], and assembly of a normal extracellular fibronectin matrix [Ohh et al, 1998].…”
Section: The Vhl Gene and Functionmentioning
confidence: 99%
“…Evenmore, Sp1 expression is temporally and spatially regulated during nephrogenesis. Interestingly, Sp1 was reported as a regulator of the Wilms' tumor (WT1) and Von Hippel -Lindau (VHL) tumor suppressor genes 44,45 that are involved in renal cancers.…”
Section: Human Gtctcactcttgttgcccaggctggagtgccat---------------------mentioning
confidence: 99%